2017
DOI: 10.1117/1.jbo.22.12.125004
|View full text |Cite
|
Sign up to set email alerts
|

Non-Euclidean phasor analysis for quantification of oxidative stress in ex vivo human skin exposed to sun filters using fluorescence lifetime imaging microscopy

Abstract: Chemical sun filters are commonly used as active ingredients in sunscreens due to their efficient absorption of ultraviolet (UV) radiation. Yet, it is known that these compounds can photochemically react with UV light and generate reactive oxygen species and oxidative stress in vitro, though this has yet to be validated in vivo. One label-free approach to probe oxidative stress is to measure and compare the relative endogenous fluorescence generated by cellular coenzymes nicotinamide adenine dinucleotides and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…In the previous approach 3,19 , cluster overlap between exogenous and endogenous species in the phasor space resulted in less accurate quantification and visualization of compound interactions at a point. However, considering the distance of a point in the phasor space to the centers of reference clusters now allows for a less biased calculation of compound contribution to a point in the treatment tissue sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous approach 3,19 , cluster overlap between exogenous and endogenous species in the phasor space resulted in less accurate quantification and visualization of compound interactions at a point. However, considering the distance of a point in the phasor space to the centers of reference clusters now allows for a less biased calculation of compound contribution to a point in the treatment tissue sample.…”
Section: Discussionmentioning
confidence: 99%
“…Visualization of drug spatial distribution for single component topical drug. Previous studies have described and demonstrated the feasibility of FLIM along with phasor analysis for the sensitive visualization and quantification of a single component topical drug distribution 3,19 . Briefly, phasor analysis transforms all temporal fluorescence decay traces represented by pixels in a FLIM image into a pair of phasor coordinates (G, S) through a Fourier transform.…”
Section: Two-photon Excitation Fluorescence Lifetime Imaging Microscomentioning
confidence: 99%
See 1 more Smart Citation
“…The non-Euclidean phasor analysis method has been described in a previously published article [17]. Briefly, the phasor analysis algorithm begins by transforming each temporal fluorescence decay trace into a pair of phasor coordinates (G, S), where G and S respectively correspond to the normalized real and imaginary components of the Fourier transform of the fluorescence decay traces evaluated at the laser repetition frequency.…”
Section: Non-euclidean Phasor Analysis For Fluorescence Contribution mentioning
confidence: 99%
“…To overcome these obstacles, pharmacokinetic studies of topical drug candidates have been recently carried out leveraging the nondestructive and noninvasive features of optical imaging methods such as multiphoton fluorescence microscopy, coherent Raman imaging and spectroscopy, and fluorescence lifetime imaging microscopy (FLIM) . These optical imaging methods show promising results for the visualization of drug distributions with molecularly specific contrast within skin at cellular and subcellular resolutions.…”
mentioning
confidence: 99%